Needs Assessment of Developing Academic Management of Schools Affiliated to the Sisters of Saint Paul de Chartres in Bangkok Based on the Concept of Career-Self-Efficacy - Ninphutsa, Wisa; Jariyarangsiroge, Apiradee (Saengtham College Journal, 2026)
The objective of this research is to study the needs assessment for developing academic management of schools affiliated to the Sisters of Saint Paul de Chartres in Bangkok, based on the concept of career self-efficacy. This study was conducted with descriptive methods. The target population consisted of all four schools affiliated with the Sisters of Saint Paul de Chartres in Bangkok. A total of 268 participants, including school directors, section leaders, department heads, and teachers, were included in the study. The research instrument was a self-developed questionnaire designed to assess the needs for developing academic management in these schools based on the concept of career self-efficacy, and the reliability was 0.982. Data analysis employed frequency, percentage, mean, standard deviation, and the Priority Needs Index (PNIModified). The results showed that the Necessity Index of overall needs assessment for development was 0.294 (PNIModified=0.294). When analyzed by areas of academic management, curriculum development had the highest need (PNIModified=0.307), followed by measurement and evaluation (PNIModified=0.305), and teaching and learning management (PNIModified=0.281). Guidance and counseling had the lowest need (PNIModified=0.270). In terms of career self-efficacy with academic management, the sub-item with the highest importance was problem-solving (PNIModified=0.307) and occupational information (PNIModified=0.300).